Equivalent mechanical parameters of oscillating rotary motors used in transport equipment - Andziulis, Arūnas; Vaupšas, Jonas; Guseinovienė, Eleonora; Didžiokas, Rimantas; Adomaitis, Danielius (Transport, 2006)
In various appliances and equipment of sundry transport means there is a lot of diverse mechanisms of periodical movement. So, the various piston or membrane pumps of fuel feeding and lubrication systems, circulation pumps, air and refrigerating coolant compressors, etc. are the typical examples of innovative and well promising application of the oscillating motors. In these cases the moving part of a motor can be directly connected to the working body of driven mechanism without the additional gears. Consequently, the drive can be simplified in design and improved in efficiency and reliability. Application of the oscillating rotary motors, if used in the aforesaid devices, strictly depends on specific properties of mechanical system of a motor aggregated with the driven mechanism and considered as the one‐piece unit on the whole. So, this study analyses how the properties of mechanical system, comprised of two moving parts interconnected eccentrically or centrically, can be evaluated by the equivalent rotational inertia, equivalent mass and by equivalent mechanical power factor which, in turn, determine the operating characteristics and basic possibilities of the motor. First Published Online: 27 Oct 2010